The Implementation of Higher-Order Thinking Skills in EFL Classroom: Teachers' Perceptions (Proceedings of the International Conference on Future of Education, 2019)
High Order Thinking Skills (HOTS) is inevitably important to develop students’ critical thinking as well as creative thinking skills in 21st century era. In the current curriculum of Indonesia, called 2013 curriculum, the government tries to promote the development of students’ critical and creative thinking by applying HOTS-based teaching in the classroom. In fact, when conducting teaching learning process, teachers are directly or indirectly influenced by their perceptions about HOTS itself. To reveal their perceptions, this study aims to investigate English teachers’ perceptions on HOTS implementation in Indonesia context. The subject of this survey is 28 pre-service and 10 in-service English teachers in high school level in Indonesia. There are four areas of HOTS perceptions which are investigated in this study namely teachers’ perceptions on planning, teachers’ perceptions on implementing, teachers’ perceptions on assessing and teachers’ perceptions on responsibility towards HOTS teaching learning activities. The result shows that in the areas of planning, implementing, and assessing, pre-service teachers show more positive result than in-service teachers. On the other hand, in the area of responsibility, in-service teachers show more positive result than pre-service teachers.
Keywords: HOTS Implementation; EFL Classroom; Teachers' Perceptions